Potret Pendidikan Islam Masa Dinasti Abbasiyah dan Kontribusinya Terhadap Pendidikan Islam Masa Sekarang - Sulhadewihana, Sulhadewihana; Salmiwati, Salmiwati (Tarbawiyah Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the brief history of the Abbasid Daula, portraits and dynamics of education during the Abbasid Daula, and the contribution of the Abbasid Daula to the development of Islamic education today. This research was conducted using a qualitative method based on library research where the researchers collected data by reading, studying, and analyzing journals, books, and articles from previous researchers that were related to the object of research. The results of the study indicate that education during the Abbasid Daula was an Islamic dynasty that brought glory to Muslims in its time when the golden age of Islam was achieved during the reign of these dynasties. And the method of education during the Abbasid Daula used 3 methods (oral, memorized, and written). The contribution of the Abbasid State to the development of education up to the present is to inculcate values ​​from various sciences